RELATO DE ATIVIDADE DE EXTENSÃO UNIVERSITÁRIA - Baú, Fernanda d. C.; Vizzotto, Gabriela; Dreher, Daniela Z.; Rios, Karina R.; Gomes, Joseila S.; Campos, Iris F. A. (Salão do Conhecimento, 2013)
Resumo